Diagnostic delay of more than 6 months contributes to poor radiographic and functional outcome in psoriatic arthritis - Haroon, Muhammad; Gallagher, Phil; FitzGerald, Oliver (Annals of the rheumatic diseases, 2015)
(1) To investigate the demographic and clinical characteristics contributing to the delay from symptom onset to the first visit to a rheumatologist; (2) to compare clinical, radiographic and patient-reported outcome measures of those who saw a rheumatologist early in their disease course with those who were diagnosed later. All psoriatic arthritis (PsA) patients, fulfilling CASPAR criteria, with an average disease duration of >10 years were invited for detailed clinical evaluation. The total lag time from symptom onset to their first rheumatological encounter was studied. The data were extracted from the referral letters and medical records. Patients were classified as early consulters or late consulters depending on whether they were seen by a rheumatologist within or beyond 6 months of symptom onset. 283 PsA patients were studied. Median lag time from the disease onset to the first rheumatological assessment of the cohort was 1.00 years (IQR 0.5-2). 30% (n=86), 53% (n=149) and 71% (n=202) of the cohort were seen by a rheumatologist within 6 months, 1 and 2 years of symptom onset, respectively. PsA patients with low education status (OR 2.09, p=0.02) and Body Mass Index (OR 0.92, p=0.01) were significantly more likely to have a diagnostic delay of >2 years. On multiple stepwise regression analysis, the model predicted significant association of late consulters with the development of peripheral joint erosions (OR 4.25, p=0.001) and worse Health Assessment Questionnaire scores (OR 2.2, p=0.004). Even a 6-month delay from symptom onset to the first visit with a rheumatologist contributes to the development of peripheral joint erosions and worse long-term physical function.